The effects of entrained debris on the basal sliding stability of a glacier. Issue 2 (20th May 2013) - Zoet, L. K.; Carpenter, B.; Scuderi, M.; Alley, R. B.; Anandakrishnan, S.; Marone, C.; Jackson, M.
Abstract : [1] New laboratory experiments exploring likely subglacial conditions reveal controls on the transition between stable sliding and stick‐slip motion of debris‐laden ice over rock, with implications for glacier behavior. Friction between a rock substrate and clasts in ice generates heat, which melts nearby ice to produce lubricating water. An increase in sliding speed or an increase in entrained debris raises heat generation and thus meltwater production. Unstable sliding is favored by low initial lubrication followed by rapid meltwater production in response to a velocity increase. Low initial lubrication can result from cold or drained conditions, whereas rapid increase in meltwater generation results from strong frictional heating caused by high sliding velocity or high debris loads. Strengthening of the interface (healing) during "stick" intervals between slip events occurs primarily through meltwater refreezing. When healing and unstable sliding are taken together, the experiments reported here suggest that stick‐slip behavior is common from motion of debris‐laden glacier ice over bedrock. Key Points: Debris entrained with in basal ice can dictate how a glacier will slide Frictional heat between clasts and bed melts ice producing lubricating water Experiments show stick‐slip is common between debris-laden ice and bedrock